National Insurance Scheme Reforms in the Caribbean - Ben Nassar, Koffie (IMF Working Papers; Working Paper ;, 2016)
Weighed down by population aging, slow economic growth, and high unemployment, National Insurance Schemes in the Caribbean are projected to run substantial deficits and deplete their assets in the next decades, raising the prospects of government intervention. With the region highly indebted, this paper quantifies the impact of three parametric reforms-freezing pension benefits for two years, raising the retirement age and increasing the contribution rate by one percentage point-that, if implemented, would put the pension schemes on a stronger financial footing. While the appropriate combination of reforms necessary to eliminate the actuarial deficits varies depending on each country's circumstances, most countries need to undertake reforms now or risk even higher taxes, lower growth and unsustainable debt dynamics.